Originality in Copyright and the Debate on Protection of Traditional Knowledge: A View on Nigerian Law - Adam, K. I.; Yusuf, I. A. (NIU Journal of Social Sciences, 2017)
Copyright is perhaps the most popular and familiar branch of intellectual property law which is used for the protection of literary, artistic, and dramatic achievements. Eligibility to copyright protection rests mainly on the requirement of originality which arguably is the main force in the creative process of all arts. Ironically, this same condition has greatly undermined the influence of copyright in so far as protection of traditional knowledge is concerned.  For instance, it is generally believed that copyright cannot protect traditional knowledge because the latter lacks originality.  Surprisingly, materials or products derived from traditional knowledge have overtime received copyright protection through their collection or compilation into books or other media of fixation.  It is for this reason that some have heavily criticized the originality requirement as ineffectual or a mere subterfuge, since it fails to stand against copyright protection of mere collection of information or ideas which were originally generated by persons other than the collectors. The truth is that the technical connotation of â€œoriginalityâ€ is not consistent with ordinary thinking whereby creativity or innovation is an integral part of an original work.  This calls the fairness of the copyright system into question. The point been made is that where a principle designed to protect an item fails to achieve its target, it should, at least, not become a tool of oppression against such item.  It thus becomes imperative that such a key principle should be re-examined to safeguard the integrity of our copyright law. It is precisely that task that has been undertaken in this paper where the nature of copyright and traditional knowledge is considered to highlight the factors of inconsistency between the two systems.  It further examines how the technical manipulation of originality has while seeking to achieve copyright objectives ended up promoting predatory activities against traditional knowledge which should ordinarily be its candidate for protection. The paper therefore argues that the system could be strengthened to at least offer negative protection of traditional knowledge where the element of innovation or creativity is read into its test of originality.  The next section examines the general notion of protection of intangible materials and its relevance to traditional knowledge.